Biotechnological Strategies of Riboflavin Biosynthesis in Microbes. (May 2022) - Zhang, Jia-Rong; Ge, Ying-Ying; Liu, Pin-He; Wu, Ding-Tao; Liu, Hong-Yan; Li, Hua-Bin; Corke, Harold; Gan, Ren-You
Abstract: Riboflavin is an essential micronutrient for humans and must be obtained exogenously from foods or supplements. Numerous studies have suggested a major role of riboflavin in the prevention and treatment of various diseases. There are mainly three strategies for riboflavin synthesis, including total chemical synthesis, chemical semi-synthesis, and microbial fermentation, the latter being currently the most promising strategy. In recent years, flavinogenic microbes have attracted increasing attention. Fungi, including Eremothecium ashbyii and Ashbya gossypii, and bacteria, including Bacillus subtilis, Escherichia coli, and lactic acid bacteria, are ideal cell factories for riboflavin overproduction. Thus they are good candidates for enhancing the level of riboflavin in fermented foods or designing novel riboflavin bio-enriched foods with improved nutritional value and/or beneficial properties for human health. This review briefly describes the role of riboflavin in human health and the historical process of its industrial production, and then highlights riboflavin biosynthesis in bacteria and fungi, and finally summarizes the strategies for riboflavin overproduction based on both the optimization of fermentation conditions and the development of riboflavin-overproducing strains via chemical mutagenesis and metabolic engineering. Overall, this review provides an updated understanding of riboflavin biosynthesis and can promote the research and development of fermented food products rich in riboflavin.